Effects of Compound Enzymes in Reduced Nutrient Density Nursery Pig Diets - Ty H. Kim; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Katelyn N. Gaffield; Ying Zhou; Xuerong Song; Xiuyi Wu; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 356 nursery pigs (DNA 241 × 600, initially 27.3 ± 0.48 lb BW) were used in a 35-d growth study to determine the effects of compound enzymes (Sunzyme; Wuhan Sunhy Biology Co., Ltd., Wuhan, P.R. China) on growth performance and nutrient digestibility in reducednutrient- density nursery pig diets. At approximately 19 d of age, pigs were weaned, randomly allotted to pens, and fed common phase 1 and 2 diets. On d 24 post-weaning, considered d 0 of the study, pigs were blocked by average pen BW and allotted to one of six dietary treatments in a randomized complete block design with four or five pigs per pen and 12 pens per treatment. Treatment diets were formulated in two dietary phases and fed from d 0 to 21 and d 21 to 35, respectively. The six treatments included a corn-soybean meal-based diet without compound enzyme (CS) and five corn-soybean meal-wheat middling-low oil DDGS-based diets (CSBP) with 0, 0.01, 0.02, or 0.03% compound enzyme 1 or 0.02% compound enzyme 2. At the conclusion of the study (d 35), fecal samples were collected from 12 pigs per treatment to determine apparent total tract digestibility (ATTD) of DM, CP, and NDF. From d 0 to 21, pigs fed the CS diet had increased (P < 0.001) ADG and improved (P < 0.001) F/G compared to pigs fed CSBP diets, but there were no treatment effects (P > 0.10) on ADFI. From d 21 to 35, pigs fed the CS diet had increased (P = 0.006) ADG and tended to have improved (P = 0.053) F/G compared to pigs fed CSBP diets. Overall, pigs fed the CS diet had increased (P < 0.001) ADG and improved (P < 0.001) F/G compared to pigs fed CSBP diets. For ATTD measures, pigs fed the CS diet had increased (P < 0.05) ATTD of DM and NDF compared to pigs fed CSBP diets. Pigs fed CSBP + 0.02% compound enzyme 1 had increased (P < 0.05) ATTD of DM, CP, and NDF compared to pigs fed CSBP + 0.02% compound enzyme 2. In summary, pigs fed the CS diet had increased ADG and ATTD of DM and NDF and improved F/G compared to pigs fed CSBP diets. Pigs fed CSBP + 0.02% compound enzyme 1 had increased ATTD of DM, CP, and NDF compared to pigs fed CSBP + 0.02% compound enzyme 2.
Keywords: carbohydrase; digestibility; growth; nursery pigs; protease